Organic beauty : an illustrated guide to making your own skincare - Godas, Maru (Smith Street Books, 2023)
"Harness the best of nature by making your own organic, natural skincare. Maru Godas celebrates nature and self-care in this beautifully illustrated guide. Decide what goes on your skin while loving both yourself and the planet. Conscious care: learn about how the different properties of the products we use can affect our bodies. Natural ingredients: discover the benefits that organic, plant-derived products can have on our skin. Recipes: make masks, scrubs, balms, butters, hair lotions and all kinds of natural skincare by following beautiful and detailed step-by-step instructions"--